EVALUASIKINERJAKEUANGANDINASKESEHATANKABUPATENPURWOREJOMELALUIPENDEKATANVALUEFORMONEY - Christiana Riyana Setiyawati (STIE Rajawali Purworejo, 2022)
This study aims to determine the evaluation of the financial performance of the Purworejo District Health Office through a value for money approach. This study used descriptivequalitativemethod. -2027wasdeclaredquiteeconomical,namely88.27%in2017becauseitwasintherangeof80%<90%andfor3(three)years.2018-2020isdeclaredaseconomicalbecauseanaverageof92.47% lies in the range of 90% -100%. However, in 2021 it was again declared quite economical at 89.54%. While the pattern of development of the level of efficiency in the financial management of the Purworejo District Health Office for 5 (five) years 2017-2021 is declared inefficient because the efficiency value is more than 100%. This is due to the existence of different work programs each year with different sources of funds even though they have minimized spending with the target. However, in 2021 it was again declared very effective. The greater the level of effectiveness achieved, the better the performance of the PurworejoHealthOffice. This is because there is realization of the budget lower than the target.